2021
DOI: 10.2298/sarh200114014n
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the venomous snakebite patients treated in the Uzice General Hospital (Western Serbia) between 2006 and 2018

Abstract: Introduction/Objective. A countrywide survey of venomous snakebites was never conducted in Serbia: the making of a central register was initiated only in 2018. We collected and analyzed the available data regarding venomous snakebites in the Uzice region (Western Serbia). The previous analysis from this hospital was published in 1968. Methods. We retrospectively analyzed the data regarding the venomous snakebite patients treated in the Uzice General Hospital between 2006 and 2018 and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Contrary to the popular belief, they are rarely fatal (Chippaux, 2012). Medical doctors in Serbia are successful in treating this medical condition (Nikolić et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Contrary to the popular belief, they are rarely fatal (Chippaux, 2012). Medical doctors in Serbia are successful in treating this medical condition (Nikolić et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…July and August (Figure 1, and Vujadinović et al, 2013). A recent study (Nikolić et al, 2021) showed that hikers/tourists usually received bites to the legs, compared to agricultural workers who were the most affected but most often received bites to the hands/arms. This difference probably resulted merely from the difference in the main activity of these two groups, not from the intention to tamper with snakes or the lack of it.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations